University extension, scientific dissemination and the right to public information: The constitution of the scientific dissemination agency of the Federal University of Amapá - Sardinha, Antonio; Vaz, Maria (Guará Journal, 2017)
Scientific dissemination is the way to expand access to scientif-ic knowledge for society as a whole, in order to help solve vari-ous social problems and bring the citizen closer to science. At the Federal University of Amapá-Unifap, there is a noticeable lack of dissemination of research. In this sense, we present the extension project Agency of Scientific Journalism, Science Unifap. The pro-posal developed a website with journalistic content involving the scientific and technological production of Unifap researchers. The project was developed based on research on strategies of scientif-ic dissemination in the field of public communication, the study of institutional production carried out by the communications sec-tor of Unifap, as well as experiences in scientific dissemination by public institutions. The production of content took as a reference the specifics of webjournalism, especially the tendency to multi-media production, using accessible language, addressing issues of public interest